Perkembangan Bahasa Ekspresif Melalui Permainan How Good Is Your Memory - Citra Laksmi Darmawanti; Sasmiati Sasmiati; Maman Surahman (FKIP UNILA, 2018)
The problem in this study was based on the lack of expressive language in children aged 4-5 years. This study aims to determine the effect of how good is your memory game activity towardd the development of expressive language in children aged 4-5 years. This study applied pre- experimental method with One Pretest-Posttest Group design. The population and sample of this study consisted of 20 children aged 4-5 years. The sampling technique was done using purposive sampling.. The data analysis technique was carried out using simple linear regression analysis to see if there was an effect of how good is your memory game activity towards children expressive language development and also t-pierd simple t-test to determine the different on the development of children expressive language. The results of this study indicated that there was an influence of how good is your memory game activity towards expressive language development of children aged 4-5 years. Masalah dalam penelitian ini adalah belum berkembangnya bahasa ekspresif pada anak usia 4-5 tahun. Penelitian ini bertujuan untuk mengetahui pengaruh aktivitas bermain how good is your memory terhadap perkembangan bahasa ekspresif pada anak usia 4-5 tahun. Metode penelitian yang digunakan adalah Pre- eksperimental dengan desain One Grup Pretest-Posttest. Populasi dan sampel pada penelitian ini berjumlah 20 anak usia 4-5 tahun. Teknik pengambilan sampel menggunakan sampling purposive. Teknik analisis data menggunakan analisis uji regresi linier sederhana untuk melihat pengaruh aktivitas bermain how good is your memory terhadap perkembangan bahasa ekspresif dan uji t pierd simple t-test untuk melihat perbedaan perkembangan bahasa ekspresif anak . Hasil penelitian ini menunjukkan bahwa ada pengaruh aktivitas bermain how good is your memory terhadap perkembangan bahasa ekspresif anak usia 4-5 tahun.Kata Kunci: permainan, how good is your memory, bahasa ekspresif